Development and performance analysis of a new solar tower and high temperature steam electrolyzer hybrid integrated plant. (19th February 2020) - Yilmaz, Fatih; Ozturk, Murat; Selbas, Resat
Abstract: In this article, an extensive thermodynamic performance assessment for the useful products from the solar tower and high-temperature steam electrolyzer assisted multigeneration system is performed, and also its sustainability index is also investigated. The system under study is considered for multi-purposes such as power, heating, cooling, drying productions, and also hydrogen generation and liquefaction. In this combined plant occurs of seven sub-systems; the solar tower, gas turbine cycle, high temperature steam electrolyzer, dryer process, heat pump, and absorption cooling system with single effect. In addition, the energy and exergy performance, irreversibility and sustainability index of multigeneration system are examined according to several factors, such as environment temperature, gas turbine input pressure, solar radiation and pinch point temperature of HRSG. Results of thermodynamic and sustainability assessments show that the total energetic and exergetic efficiency of suggested paper are calculated as 60.14%, 58.37%, respectively. The solar tower sub-system has the highest irreversibility with 18775 kW among the multigeneration system constituents. Solar radiation and pinch point temperature of HRSG are the most critical determinants affecting the system energetic and exergetic performances, and also hydrogen production rate. In addition, it has been concluded that, the sustainability index of multigeneration suggested study has changed between 2.2 and 3.05. Highlights: A novel solar energy based multigeneration system for useful outputs commodities is proposed. Solar energy is used in the suggested system as the heat source. The proposed study is analyzed with thermodynamics methods, which are energy and exergy efficiencies viewpoints. Total energetic and exergetic performance of suggested paper are calculated as 60.14%, 58.37%, respectively.